2018
DOI: 10.2217/pgs-2017-0195
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenetics of Oral Antidiabetic Therapy

Abstract: Type 2 diabetes prevalence is still on the rise worldwide. Antidiabetic drugs are widely prescribed to patients with Type 2 diabetes. Most patients start with metformin which is mostly well tolerated. However, a high percentage of patients fail to achieve glycemic control. The effectiveness of metformin as well as most other antidiabetic drugs depends among other factors on interindividual genetic differences that are up to now ignored in the treatment of Type 2 diabetes. Interestingly, many genes influencing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 95 publications
0
12
0
Order By: Relevance
“…Several guidelines, including ADA, recommended achieving a range of 6.5–7% for good glycemic control and minimal risks for the associated complications 38 . Pharmacogenetic studies could help in investigating and identifying those variabilities seen in practice between patients receiving oral hypoglycemic agents 11 , 12 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several guidelines, including ADA, recommended achieving a range of 6.5–7% for good glycemic control and minimal risks for the associated complications 38 . Pharmacogenetic studies could help in investigating and identifying those variabilities seen in practice between patients receiving oral hypoglycemic agents 11 , 12 .…”
Section: Discussionmentioning
confidence: 99%
“…Both drugs decrease blood glucose by different mechanisms, metformin decreases the hepatic glucose production, and acts as insulin sensitizer, while sulfonylureas lower blood glucose by increasing insulin secretion 10 . There is a great variation in response to many oral hypoglycemics, interestingly up to 40% of inter-individual variabilities could be explained by genetic factors 11 , 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Metformin might induce lactic acidosis in patients with renal insufficiency, therefore it is not prescribed in this subgroup of patients with T2D. 5 To Other mechanisms of the hypoglycemic effect of metformin include glucoagon-dependent antagonism of glucose output from hepatocytes by reducing cyclic AMP production, and inhibition of glucose hepatic mitochondrial glycerophosphate dehydrogenase.…”
Section: Metforminmentioning
confidence: 99%
“…An updated review concluded that the addition of a sulfonylurea to metformin persists the most cost-effective second-line therapy for patients when compared to other drugs (Sodium-glucose co-transporter-2 inhibitors, dipeptidyl-peptidase inhibitors and Glucagon-like peptide-1receptor agonist) [ 11 ]. Despite this, it is becoming increasingly evident that the treatment outcome with oral anti-diabetics differs strongly between individuals and that a personalized approach would make sense [ 12 ].…”
Section: Introductionmentioning
confidence: 99%